2012
DOI: 10.1155/2012/125367
|View full text |Cite
|
Sign up to set email alerts
|

Urticaria in Monozygotic and Dizygotic Twins

Abstract: Aim. To identify risk factors for urticaria, to determine the relative proportion of the susceptibility to urticaria that is due to genetic factors in an adult clinical twin sample, and to further determine whether the genetic susceptibility to urticaria overlaps with the genetic susceptibility to atopic diseases. Methods. A total of 256 complete twin pairs and 63 single twins, who were selected from sibships with self-reported asthma via a questionnaire survey of 21,162 adult twins from the Danish Twin Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The prevalence of urticaria documented in the present study (11.0%) is higher than in all past surveys 5,6,8 but is comparable with the 8.8% documented by Zuberbier et al 25 The higher prevalence of urticaria among females (64.3%) in the current series is similar to the 70.3% reported by other workers. 25,26 Similarly, Thomsen et al 26 have previously shown that female gender, AD, and hay fever are risk factors for urticaria. New studies are needed to confirm other associations, such as those with monozygotic twin status, metabolic syndrome, 27 human leukocyte antigen (HLA)-B50, anti-thyroid peroxidase enzyme, and presence of antinuclear antibodies among Nigerians.…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of urticaria documented in the present study (11.0%) is higher than in all past surveys 5,6,8 but is comparable with the 8.8% documented by Zuberbier et al 25 The higher prevalence of urticaria among females (64.3%) in the current series is similar to the 70.3% reported by other workers. 25,26 Similarly, Thomsen et al 26 have previously shown that female gender, AD, and hay fever are risk factors for urticaria. New studies are needed to confirm other associations, such as those with monozygotic twin status, metabolic syndrome, 27 human leukocyte antigen (HLA)-B50, anti-thyroid peroxidase enzyme, and presence of antinuclear antibodies among Nigerians.…”
Section: Discussionmentioning
confidence: 94%
“…Risk factors reported for AU include high population density 15 and personal 32 and parental history of allergic diseases 2,33 . Higher prevalence and/or higher risk of having AU may be associated with poverty and lower socio-economic status 14,15 , whereas risk for CU was linked to high income and socio-economic status in some studies 2, 23,34 but not all 35,36 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Higher prevalence and/or higher risk of having AU may be associated with poverty and lower socio-economic status 14,15 , whereas risk for CU was linked to high income and socio-economic status in some studies 2, 23,34 but not all 35,36 . In studies involving twins, genetic factors could partly explain susceptibility to urticaria 32 . The role of polymorphisms of several genes, including TNFRS11A, TBXA2R and PLA2G4A 37 , has been suggested in susceptibility to AU and/or angioedema induced by multiple NSAIDs.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Most cases are acute, lasting no more than 6 weeks, and can be precipitated by multiple factors, including intercurrent illness, medicines, food, and altitude. [2][3][4][5] Cutaneous mast cells play an essential etiologic role. 6 IgE is thought to bind to CD23 and FceRI on mast cells and other immune effector cells.…”
Section: Introductionmentioning
confidence: 99%